Advances in the detection technology of vegetable soil borne fungi and bacteria - Chen, Lida; Lü, Guiyun; Yang, Songhan; Gong, Binbin; Lu, Yusong; Wu, Xiaolei; Li, Jingrui; Gao, Hongbo (Frontiers in Microbiology, 2024)
Soil borne diseases are one of the most serious diseases which often results the decline of vegetables quality and loss of production. Moreover, it is difficult for plants to exhibit disease symptoms in the early stages attributing to strong concealment of soil borne pathogens. Therefore, early detection of pathogens and their physiological races plays an important role in reducing the harm of pathogens associated with diseases of vegetable crops. The traditional diagnostic techniques relied on the time consuming and less accurate methods like disease symptom observation, microscopic diagnosis, and culture techniques etc. The development of molecular biology technology has brought revolutionary changes to the diagnosis of vegetable soil borne diseases, improving the accuracy and efficiency of diagnosis. This paper reviews the various molecular detection techniques for vegetable soil borne pathogens (PCR, nested-PCR, multiplex PCR, etc.) and their physiological races (host identification, DNA molecular markers, transposon detection, etc.), explains the advantages and disadvantages of each detection technique. Furthermore, the paper comprehensively introduces the application of molecular detection technology for soil borne pathogen detection in soil, plants, and seeds. Finally, we put forward important perspectives for the future development of rapid detection methods, aiming to promote rapid diagnosis of soil pathogenic microorganisms and provide guidance for the control of biological risks.